2016
DOI: 10.1016/j.acmx.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre el sistema IGF y PAPP-A en ateroesclerosis coronaria

Abstract: Atherosclerosis is a condition that involves multiple pathophysiological mechanisms and whose knowledge has not been fully elucidated. Often, scientific advances on the atherogenic pathophysiology generate that molecules not previously considered in the scene of this disease, were attributed actions on the onset or progression of it. A representative example is the study of a new mechanism involved in the atherogenic process, consisting of the association between the insulin-like growth factor (IGF) system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Outside the realm of pregnancy, PAPP-A has been investigated for its association with cardiovascular risk, underscoring its broad relevance to human health 13 . The literature describes its involvement in a variety of physiological and pathological processes, including metabolism, cancer, and neurodegenerative diseases 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Outside the realm of pregnancy, PAPP-A has been investigated for its association with cardiovascular risk, underscoring its broad relevance to human health 13 . The literature describes its involvement in a variety of physiological and pathological processes, including metabolism, cancer, and neurodegenerative diseases 14 .…”
Section: Discussionmentioning
confidence: 99%
“…33 The possible reason could be that local IGF-I in coronary atherosclerosis stimulates vascular smooth muscle cell proliferation and releases inflammatory factors leading to vulnerable plaques. 34,35 Due to the complexity of IGF system function, clinical implications vary in different disease populations.…”
Section: Discussionmentioning
confidence: 99%
“… 33 The possible reason could be that local IGF-I in coronary atherosclerosis stimulates vascular smooth muscle cell proliferation and releases inflammatory factors leading to vulnerable plaques. 34 , 35 Due to the complexity of IGF system function, clinical implications vary in different disease populations. A large prospective study found that the association between free IGF-I and T2DM varied by insulin levels, 36 and indicated an inverse association limited to subjects with higher levels of insulin.…”
Section: Discussionmentioning
confidence: 99%